See (n)One, Do (n)One, Teach (n)One: Reality of Surgical Resident Training in Germany - Huber, T. (World J Surg, 2020)
INTRODUCTION: Due to technological changes, working time restrictions and the creation of specialized centers, surgical training has changed. A competence-based learning technique of surgical skills is the sub-step practice approach, which has been proven important in nationwide opinion surveys. The aim of this prospective multi-center trial was to determine the status quo of the sub-step concept in Germany. METHODS: Over 6 months, the voluntarily participating centers evaluated the following index procedures: laparoscopic cholecystectomy (LCHE), laparoscopic and open sigmoid resection, minimally invasive inguinal hernia repair, thyroid resection and pylorus-preserving pancreaticoduodenectomy (PPPD). Patients with private insurance were excluded. The detailed sub-steps were documented as well as the reason why these were not performed. In addition, an online survey regarding the sub-step concept was performed before and after the study. RESULTS: In total, 21 centers included 2969 surgical procedures in 2018 for final analyses. While 24.4% of the procedures were performed by residents, sub-steps were performed in 22.2%. LCHE was most often performed completely by residents (43.3%), and PPPD revealed the highest rate of performed sub-steps (43.3%). Reasons for not assisting sub-steps to residents were often organizational and other reasons. After an initial increase, the number of performed sub-steps decreased significantly during the second half of the survey. The opinion survey revealed a high importance of the sub-step concept. The number of resident procedures was overestimated, and the number of performed sub-steps was underestimated. After the study, these estimations were more realistic. CONCLUSION: Even though the sub-step practice concept is considered highly important for surgical education, it needs to be put into practice more consequently. The current data suggest a low participation of surgical residents in the operating room, although the participating hospitals are most likely highly interested in surgical education, hence their voluntary participation. Conceptual changes and a control of surgical education are needed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00268-020-05539-6) contains supplementary material, which is available to authorized users.